(untitled) (International journal of artificial intelligence, 2025)
This article explores how digital platforms are fundamentally reshaping the service sector by enhancing accessibility, efficiency, and personalization. It analyzes the core functions of digital platforms, the technological innovations driving this shift, and the economic and social impacts on service delivery. The study highlights how sectors such as transportation, healthcare, education, and finance are evolving through platform-based models. Furthermore, it examines the challenges and regulatory considerations associated with this transformation.